Analyzing the Performance of an Externally Journaled Filesystem - Rocha, Pedro Eugênio; Bona, Luis C. E. (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC); 2012: Anais do II Simpósio Brasileiro de Engenharia de Sistemas Computacionais, 2012)
Journaling is a common technique used by current filesystems to ensure data consistency in face of a crash. Because the journal is often stored as a file within the filesystem, journal and fixed-position writes are likely to compete for disk bandwidth, posing a considerable overhead to the storage system. In order to isolate journal and fixed-position traffic, some filesytems allow the journal to be stored in an external device, thereby allowing the exploitation of parallelism and increasing the spatial locality. In this paper we analyze the performance of an externally journaled filesystem under different scenarios and journaling modes and compare it to a traditional journaled filesystem. We found that ordered and writeback journaling modes in an external device can obtain about 40% of performance improvement in a mail server workload if compared to a traditional journaled filesystem; in addition, we also observed that data journaling mode can provide substantial performance gains under very specific workloads.